Late Neolithic Zaisan Archeological Culture in Primor'e (the South of Russia's Far East): A History of Ideas and Conceptions. Issue 1 (3rd April 2019) - Krutykh, Evgeniy B.; Batarshev, Sergey V.
Abstract : The history of ideas and conceptualizations formed over the past fifty years and more in the study of the Late Neolithic of the south of Russia's Far East (Primor'e) is examined. According to predominant views, Primor'e's Late Neolithic is represented by sites of one archeological culture—the Zaisan. However, the large number of excavated sites, the vivid and diverse archeological material, and differences in methodological and theoretical approaches used by researchers in interpreting the complexes studied has led to numerous treatments of the concept of a "Zaisan archeological culture." The authors here view the history of the ideas and concepts in the study of the Zaisan culture as one method of scholarly reflection. Such an approach allows the essence and logic of opinion differences among researchers to be determined. Focus is on questions discussed in the scholarly community, permitting the most important and promising problems for further study to be identified.